An investigation of the YidC-mediated membrane insertion of Pf3 coat protein using molecular dynamics simulations - Polasa, Adithya; Hettige, Jeevapani; Immadisetty , Kalyan; Moradi, Mahmoud (Frontiers in Molecular Biosciences, 2022)
YidC is a membrane protein that facilitates the insertion of newly synthesized proteins into lipid membranes. Through YidC, proteins are inserted into the lipid bilayer via the SecYEG-dependent complex. Additionally, YidC functions as a chaperone in protein folding processes. Several studies have provided evidence of its independent insertion mechanism. However, the mechanistic details of the YidC SecY-independent protein insertion mechanism remain elusive at the molecular level. This study elucidates the insertion mechanism of YidC at an atomic level through a combination of equilibrium and non-equilibrium molecular dynamics (MD) simulations. Different docking models of YidC-Pf3 in the lipid bilayer were built in this study to better understand the insertion mechanism. To conduct a complete investigation of the conformational difference between the two docking models developed, we used classical molecular dynamics simulations supplemented with a non-equilibrium technique. Our findings indicate that the YidC transmembrane (TM) groove is essential for this high-affinity interaction and that the hydrophilic nature of the YidC groove plays an important role in protein transport across the cytoplasmic membrane bilayer to the periplasmic side. At different stages of the insertion process, conformational changes in YidC's TM domain and membrane core have a mechanistic effect on the Pf3 coat protein. Furthermore, during the insertion phase, the hydration and dehydration of the YidC's hydrophilic groove are critical. These results demonstrate that Pf3 coat protein interactions with the membrane and YidC vary in different conformational states during the insertion process. Finally, this extensive study directly confirms that YidC functions as an independent insertase.